An Analytical Study of Quality Circles in Hospitals in India for Improving Productivity of Administrative Staff: Developing an Effective Model for Hospital Quality Circles in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The aim of this research study is to explore the essence of Indian Hospital Quality Circles (QCs) and their effect on hospital administration and the well-being of staff forming QC teams. Although QCs were first initiated in Japan in the early 60s and eventually came to India only in the 80s, this study supports that value added in the current healthcare industry can be extracted from the practice of QC instruments and techniques. The projects are selected by the members because QCs are voluntary in nature, and their performance rate has been shown to be high and impactful. This research supports the fact that there has been an improvement in productivity in the areas where the QC programmes have been implemented, although it is not conclusively indicative of an overall increase in hospital productivity. The significance of this study is that while still in a nascent stage in Indian Hospitals and used only by early adopters, its growth is likely to continue if QCs meet workers at the grass root level and are assisted by other quality systems of healthcare. Since quality is one of the main drivers of the healthcare industry, this study is intended to be important and useful for hospital management, staff and healthcare professionals to recognize relevant areas of improvement in their workplace and to find participatory solutions for them. This study suggests a model for clearly institutionalizing and operating hospital quality circles by combining the principles of QCs and the unique requirements of hospitals. The model also recommends such criteria with modifications for hospital QCs to meet the needs of the industry, such as group sizes, frequency and documentation specifications. This is very much associated with the newer Lean QCs definition introduced by India's Quality Circle Forum (QCFI). In the report, the causes that have contributed to certain hospital QCs being inactive have been illustrated and can be thoughtfully avoided and removed by this approach by practitioners.